Technical cellulose as an adsorbent of copper and chromium ions - Marina Šćiban; Dragana Kukić; Jelena Prodanović; Mile Klašnja (Zaštita Materijala)
The presence of heavy metals in the natural environment is mainly due to the rapid industrial development and it is a significant problem in terms of environmental protection. Due to their toxicity and bioaccumulation it is necessary to remove them from industrial effluents. One of the most commonly applied method is adsorption by various adsorbents of biological origin - biosorbents. In recent years, attention is drawn to lignocellulose materials which meet the basic requirements for adsorbents: relatively good adsorption efficiency, availability in large quantities and a low price, because they often occur as waste material. Basic components of lignocellulosic materials are cellulose, lignin and hemicelluloses. In this paper the adsorption properties of cellulose was investigated in order to assess its contribution to adsorption capacity of these complex materials. The adsorption of nickel, copper, zinc, cadmium and chromium ions by pulp, was investigated. To describe the process, different models of adsorption isotherms were applied. The results showed that, according to Langmuir's constants, pulp has the highest adsorption capacity for cadmium and chromium ions, and the lowest for zinc ions.